2013
DOI: 10.1523/jneurosci.5027-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Efferent Feedback Minimizes Cochlear Neuropathy from Moderate Noise Exposure

Abstract: Although protective effects of the cochlea’s efferent feedback pathways have been well documented, prior work has focused on hair cell damage and cochlear threshold elevation and, correspondingly, on the high sound pressure levels (> 100 dB SPL) necessary to produce them. Here we explore the noise-induced loss of cochlear neurons that occurs with lower intensity exposures and in the absence of permanent threshold shifts. Using confocal microscopy to count synapses between hair cells and cochlear nerve fibers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
199
2
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(213 citation statements)
references
References 50 publications
(80 reference statements)
6
199
2
6
Order By: Relevance
“…The nervous system can set the value of the threshold by using efferent feedback. For example, hearing loss to sound intensities that normally would not produce deafness can arise because of a failure of efferent feedback in the cochlear nucleus [59]. The observation that the detection threshold for ankle proprioception depends on muscle tension in the calf muscles [79,80] raises the question as to whether detection thresholds for balance can be similarly adjusted by adopting different postures while standing.…”
Section: Stimulus Amplitudementioning
confidence: 99%
“…The nervous system can set the value of the threshold by using efferent feedback. For example, hearing loss to sound intensities that normally would not produce deafness can arise because of a failure of efferent feedback in the cochlear nucleus [59]. The observation that the detection threshold for ankle proprioception depends on muscle tension in the calf muscles [79,80] raises the question as to whether detection thresholds for balance can be similarly adjusted by adopting different postures while standing.…”
Section: Stimulus Amplitudementioning
confidence: 99%
“…The MOCR may be essential for normal development of cochlear active mechanical processes (Walsh et al 1998), and/or to minimize deleterious effects of noise exposure on cochlear function (Maison et al 2013). A more widely accepted role is that the MOCR possibly facilitates understanding speech in noisy environments.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, vulnerability of the mouse cochlear nerve to TTS increases when the LOC efferents are removed [10]. An antiexcitotoxicity role of the LOC system has been suggested [10,38,46]. It is difficult to measure the LOC, but there is some speculation that MOC and LOC strengths are related in individuals [35], so LOC strength might be inferable from MOC strength.…”
mentioning
confidence: 99%
“…Recent work has shown that another effect of noise damage, even at moderate noise-exposure levels that do not result in permanent hearing loss, is a permanent cochlear-nerve deficit affecting high-threshold, low-and medium-SR fibers [15,29], which are important for supra-threshold temporal processing [2]. The underlying cause presumably is glutamate excitotoxicity [38]. Why it preferentially affects low-and medium-SR fibers is not known [2] but may be due to low mitochondrial content [38].…”
mentioning
confidence: 99%
See 1 more Smart Citation